The Impact of Good Corporate Governance and Corporate Social Responsibility (CSR) Disclosure on Tax Avoidance Practice: Empirical : Study on Multinational Companies in Idonesia - Anggun Cahyanti Simanjuntak; Susi Sarumpaet (International Journal of Economics and Management Sciences, 2026)
This research aims to investigate the impact of Good Corporate Governance (GCG) which are measured by 3 indicators; institutional ownership, managerial ownership, board indeoendence, and Corporate Social Responsibility Disclosure on Tax Avoidance in Multinational Companies on Indonesia. The study used multiple linear regression with periods start from 2022 until 2024. The sample of this study is a multinational companies in Indonesia with the total of 47 samples for 3 years, the criteria of the company can be said multinational companies is if the companies had a entities in more than one country. Tax avoidance is measured using the Cash Effective Tax Rate (CETR), while GCG variables and CSR disclosure are measured based on relevant ownership structures, board composition, and the Global Reporting Initiative (GRI) index. The result shows that Institutional ownership had a significantly negative effect of tax avoidance, while the other three independent variables had no significant power in Tax Avoidance. This study concludes that tax avoidance in multinational companies is a complex phenomenon influenced by various internal and external factors beyond the scope of this research. The findings provide practical implications for regulators and investors and suggest that future research should consider additional variables, longer observation periods, and alternative tax avoidance proxies.